Karang Gading and Langkat Timur Laut as wildlife game reserve, that are covered by mangrove forest and are potential region in supporting local and migratory bird life, are one of conservation area in North Sumatera Province. Increasing population number of people surrounding the project area was also followed by the increasing of live needs Gading Beach, which is very susceptible with conversion and high exploitation. The conflict interest requently occurs in case of converting land that caus - Adil .; Dedei Setiad; Jarwadi B. Hernowo (Forum Pasca Sarjana, 2010)
Karang Gading and Langkat Timur Laut as wildlife game reserve, that are covered by mangrove forest and are potential region in supporting local and migratory bird life, are one of conservation area in North Sumatera Province.  Increasing population number of people surrounding the project area was also followed by the increasing of live needs Gading Beach, which is very susceptible with conversion and high exploitation.  The conflict interest requently occurs in case of converting land that caused impact to ecology and economy of properties, and indirectly affect to the decreasing of bird diversity.  The objectives of this research were to analyze the relationships between the structure and composition of tree species and the bird biodiversity.  The research was conducted from June to September 2007 in the Karang Gading Beach and Langkat Timur Laut Wildlife game reserve, North Sumatera Province.  The sampling area was selected four subhabitats consisting of (1) primary mangrove subhabitat, (2) Secondary mangrove subhabitat, (3) intensif embankment subhabitat, and (4) extensive embankment subhabitat.  A purposive sampling method was applied for mangrove vegetation, and IPA (indices ponctuels d’abundances) and CC (concentration counts) method were used for bird observe.  Results showed that there significant relationships between the structure and composition of tree species and the bird biodiversity in all subhabitats.  The correlation coefficient in primary mangrove subhabitat was higher than those of the other subhabitats.  The correlation coefficients of 0.86, 0.92. 0.85, and 0.93 were for primary mangrove. Secondary mangrove, intensive embankment and extensive embankment subhabitat, respectively.  Hight variety of tree species in each subhabitat could increase the bird diversity.   Key words: structure and composition, mangrove, bird biodiversity